KARAKTERISTIK FISIK LAHAN AKIBAT ALIH FUNGSI LAHAN HUTAN RAWA GAMBUT(Physical characteristic of peat land use change of peat swamp forest) - Nusantara, Rossie Wiedya; Sudarmadji, .; Djohan, Tjut Sugandawaty; Haryono, Eko (TOP lndonesia, 2013)
The aim of this study is to investigate physical characteristic of peatlands and peat soils at five land use types (primary peat swam forest-HP, secondary peat forest-HS, sbrub-SB, oil palro-KS, cornfield-KJ), such as ground water table, depth of peat soi l, thickness of peat composition, depth of organic material(humus), bulk density-BD, porosity and soil water content as effect of land use change. This study was conductend at peatland in Rasau Jaya- West Kalimantan Province. Result of the study show that at HP and HS have deeper ground water table, deeper depth of peat soils, soil maturity level varies with thinner depth of peat composition, organic material on forest floor than at KS and KJ. Result of phsical properties of peat soils show that at KJ have higher BD, KS have higher prosity and KS and KJ have shallower soil water content than at HP or HS. The differences is caused the contruction of drainage canals causing an excessive loss of water, prior to reclamation activities may result in the drop of depth of ground water table. This will generally to followed by an increase in tbe rate of peat decomposition and changes in the physical properties of peat.